An intracardiac accessory thyroid gland mimicking cardiac tumor: A case report and literature review. Issue 51 (December 2017) - Wang, Lin-Jing; Liu, Chun-Mei; Chen, Xin; Zhang, Li; Zhou, Hong-Wei
Abstract: Rationale: An accessory thyroid gland (ATG) in the right ventricle is an extremely rare condition. Described herein are histological findings of ATG in the right ventricle found in a patient with a normal cervical thyroid gland. Patient concerns: A 53-year-old woman was referred to our hospital after experiencing intermittent precordial pain for 2 years. Diagnoses: The mass in the right ventricle was diagnosed pathologically as ATG. Interventions: Complete excision was performed because of the patient's intermittent precordial pain and to exclude the possibility of malignancy. Outcome: The patient's pain was resolved. No recurrence was observed during the 6-month follow-up. Lessons: After review and analysis of the case, we found that plain and contrast-enhanced computed tomography scans showed that the mass had a similar intensity and enhancement to a cervical thyroid gland, which we think may be a useful clue for making a preoperative diagnosis of ATG.